The B-Vitamin Mutualism Between the Dinoflagellate Lingulodinium polyedrum and the Bacterium Dinoroseobacter shibae - Cruz-López, Ricardo; Maske, Helmut; Yarimizu, Kyoko; Holland, Neal A. (Frontiers in Marine Science, 2018)
Recent research has shown that in aquatic systems pairs of prokaryote and eukaryote species exercise symbiotic exchanges of metabolites that are essential for the proliferation of either species. Using dinoflagellate Lingulodinium polyedrum cultures and a factorial design, we examined its growth at different concentrations of vitamin B1 (thiamine) and B12 (cobalamin). When both vitamins were at their lowest concentrations tested, 0.033 pM of B1 and 0.053 pM of B12 the growth was limited. When axenic L. polyedrum was co-cultured with the bacterium Dinoroseobacter shibae, a known B1 and B12 producer, then L. polyedrum grew at the same rate as in culture media supplemented with B1 and B12. In the L. polyedrum vitamin - limited culture (V-L), the abundance of attached and free-living D. shibae was higher than in the vitamin - replete (V-R) culture. In the V-R and V-L co-cultures the measured particulate B12 (pB12) concentration of attached and free-living D. shibae were in the range of 4.7x10-19 to 3x10-18 and 8.4x10-21 to1.2x10-19 (mol cell-1) respectively. Without B12 or B7 (biotin) added to the culture medium of a co-culture of L. polyedrum and D. shibae, the measured dissolved B12 (dB12) concentration was more than 60 pM higher than necessary for un-limited growth rates of L. polyedrum. In the same culture we measured B7 in the L. polyedrum particulate fraction (pB7; 4.7x10-19 to 9.4x10-19 mol cell-1). We suggest that in response to the production of B1 and B12 by D. shibae to supply L. polyedrum requeriments, the latter produced B7, which is required by D. shibae, and in our culture was only produced by L. polyedrum when D. shibae was present. We propose that D. shibae can control L. polyedrum through the release of B1 and B12, and L. polyedrum can control D. shibae through the release of B7. D. shibae is also auxotroph for niacin and 4-amino-benzoic acid, not provided by the culture medium. Therefore, L. polyedrum might affect a similar control through the release of these specific compounds and organic substrate necessary for the growth of D. shibae.